Analysis of the Role of Farmer Groups in Increasing the Income of the Community of Jumateguh Village, Bunturaja District - Sonia Simamora; Yusnadi; Muhammad Takwin Machmud (PT. Global Research Collaboration, 2023)
This study aims to explain the role of farmer groups in increasing the income of the people of Jumateguh Village, Banturaja District. The qualitative approach using descriptive methods and data collection techniques including observation, interviews, and documentation. The results shows there are three roles of farmer groups in the Jumateguh village community, namely as a forum for discussion for group members in solving a problem by finding solutions together through discussion forums, secondly as a forum for information for group members in obtaining information from extension agents regarding how to choosing good/superior plant seeds, as well as handling pests and diseases that attack plants, and the third as a production unit, namely providing production facilities and infrastructure such as tanks for spraying pesticides and insecticides on plants and tripe machines to clean grass that disturbs plants.